Treatment of Pelvic Organ Prolapse in a Patient with a Thermal Burn Wound Caused by Hot Stone Therapy, a Traditional Thai Treatment - Srisukho, Sasivimol (Case Rep Obstet Gynecol, 2017)
A 72-year-old woman presented with a 1-month history of an incarcerated uterine prolapse along with an infected wound at the anterior uterine wall. She had previously undergone the traditional Thai practice Yue Fai, or “lying by the fire,” as performed by postpartum women. However, her uterus was burned by the extremely high temperature involved in the practice; it subsequently became infected and incarcerated. Pelvic examination revealed stage IV genitourinary prolapse according to the POP-Q classification. An ill-defined ulcer measuring 6.5 × 4.5 cm was present in the anterior wall of the uterus, and a 2.0 cm diameter ulcer was present in the right posterior wall of the uterus. The patient was treated symptomatically with broad-spectrum antibiotics, local estrogen therapy, analgesic and anti-inflammatory agents, and antiseptic dressing of the ulcerated area. After alleviation of all symptoms, the ulcer almost completely healed. She was advised to undergo definitive surgical treatment for the prolapsed uterus.